The Success Of Zakat Distribution And Aids For Sustaining Muallaf (New Convert) Belief And Thought: A Case Study - Fuadah Johari; Muhammad Ridhwan Ab. Aziz; Mohd Faisol Ibrahim; Nursilah Ahmad; Ahmad Fahme Mohd Ali; Kalsom Abd Wahab; Khadijah Hambali; Zainal Abidin Mohamed (Universiti Sains Islam Malaysia, 2024)
Zakat is one of the pillars of Islam that emphasises the socio-economic development. Any discussion on zakat in the context of worship cannot be disconnected from the socioeconomic factor, especially in aiding the underprivileged. The primary purpose of zakat is to redistribute wealth of the society among the poor. Zakat is not purely welfare-oriented that relies on the contribution of the giver but an obligation that must be carried out to qualified recipients.Therefore, it is pertinent that the management of zakat is made efficient to ensure that the rights of the recipients and the society, in general, will not be put in jeopardy. The question is then raised regarding the type of zakat distribution or programmes pertaining to the asnaf Muallaf. The objective of this article is to explore challenges and the success of zakat distribution and aids for sustaining muallaf belief (Tauhid) and thoughts (Iman). The methodology of this article is based on qualitative research through document analysis and interview with zakat officer and respondents. This article has revealed that some challenges and success perception said by the Muallaf as the zakat recipient benefited from the zakat aids. Results show that State Islamic Religious Council should continue support and to improve from time to time to a more comprehensive program that focus on sustaining the Muallaf belief (Tauhid) and thoughts (Iman).